MEMAHAMI KONFLIK ANTARAKTOR DALAM IMPLEMENTASI SISTEM INFORMASI PERGURUAN TINGGI : PERSPEKTIF TEORI STAKEHOLDER - Mohammad Muhsin (MULTITEK INDONESIA, 2017)
College is a provider of higher education, both public and private sector. Information is a strategic resource as one factor in determining success university management, the implementation of information systems become an integrated part of the overall academic process engineering. But the reality is not so. This study examines the causes of conflict between actors in the implementation of the information system of higher education in the context of stakeholder theory, the causes of conflict, due to the conflict and a solution to the conflict. The method used in this study is the interpretive method is to look for an explanation of eventsthat are based perspectives and experience of the actors studied. Data collection techniques in this study is a direct informer interviews with semi-structured approach. The analysis shows there are two kinds of conflict between actors ie technical and non technical factors. Technical factors are relatively easy to find a solution that is suitable software application. This non-technical factors concerning human resources associated with stakeholders around the core of the problem. This is an actor stakeholder policy makers, so the need to search root of the problem as the solution appropriate and more focused on the problems of each actor. In the implementation of the information system of universities need to consider aspects of demand and supply, only mendevelop of culture and characteristics that match the user culture